Uganda : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix analyzes poverty and social development in Uganda. The paper reviews recent poverty and inequality trends, examines how poor people are coping with risk and vulnerability, analyzes the relationship between economic growth, structural reform and poverty, and describes the government policies in these areas. The paper also provides a brief overview of major institutional developments in Uganda's financial sector since 1993 with regard to the legal, accounting, and general regulatory framework in which financial institutions operate.